Determination of environmental lead pollution in Alawi el-hilla and Bab-almudam bus stations in Baghdad city (Baghdad Science Journal, 2011)
Two main grand bus national stations in Baghdad ( Alawi-alhila and Bab-almudam) were chosen as examples to determine lead effect on its drivers. This lead came from ethyl tetra lead or ethyl tri lead which used to improve gasoline quality ,so these two stations could be consider as two of the most polluted places due to gasoline burned by hundreds cars located in these stations .The determination of environmental lead pollution was measured in blood and urines drivers. Drivers were divided in two main groups due to their ages ( 30 persons in each group). The first group for men of 22-30 years old. The second group for men of 40-60 years old. Those men were carefully chosen in order to be non-fumiers or non-alcoholics persons because of the presence of lead in alcohol and cigarettes products .The results prove the presence of high pollution levels of lead in the second group : 35ug/dl in blood and 178 ug/l in urine.